(untitled) (Research, Society and Development, 2022)
The term BRICS, referring to the emerging countries Brazil, Russia, India, China and South Africa, aroused interest of many investors. However, there are still few studies that evaluate the evolution of trade flows between Brazil and BRICS, especially with Russia. This study analyzed the importance of BRICS (Brazil, Russia, India, China and South Africa) for the Brazilian wood pulp segment’s trade flow with Russia from 1997 to 2016, comparing the period before and after of the formation of BRICS. The Indexes of Trade Intensity, Regional Orientation, Grubel and Lloyd and Menon and Dixon were used as methodological tools. The obtained results indicated that the formation of the BRICS was very important for the Brazilian wood pulp trade with Russia; trade between these nations has intensified; and the trade pattern proved to be inter-industrial. Thus, it is believed that trade between Brazil and Russia is promising and should be encouraged, as well as the BRICS.